Assessing sex differences in viral load suppression and reported deaths using routinely collected program data from PEPFAR-supported countries in sub-Saharan Africa - Danielle Fernandez; Hammad Ali; Sherri Pals; George Alemnji; Vamsi Vasireddy; George K. Siberry; PEPFAR MER Interagency Participants; Ikwo Oboho; Catherine Godfrey (BMC, 2023)
Abstract Background In sub-Saharan Africa, more women than men access HIV testing and treatment and may have better viral load suppression (VLS). We utilized routinely reported aggregated HIV program data from 21 sub-Saharan African countries to examine sex differences in VLS and death rates within antiretroviral therapy (ART) programs supported by the United States President's Emergency Plan for AIDS Relief (PEPFAR). Methods We included VLS and reported death data for persons aged 15 + years on ART from October-December 2020 disaggregated by sex and age for each subnational unit (SNU). We used linear mixed-model regression to estimate VLS proportion and negative binomial mixed-model regression to estimate the rates of death and death plus interruptions in treatment (IIT). All models were weighted for SNU-level ART population size and adjusted for sex, age, HIV/tuberculosis coinfection, country, and SNU; models for reported deaths and deaths plus IIT were also adjusted for SNU-level VLS. Results Mean VLS proportion was higher among women than men (93.0% vs. 92.0%, p-value < 0.0001) and 50 + than 15-49 age group (93.7% vs. 91.2%, p-value < 0.0001). The mean rate of reported deaths was higher among men than women (2.37 vs. 1.51 per 1000 persons, p-value < 0.0001) and 50 + than 15-49 age group (2.39 vs. 1.50 per 1000, p-value < 0.0001); the mean rate of reported deaths plus IIT was higher among men (30.1 in men vs. 26.0 in women per 1000, p-value < 0.0001) and higher among 15-49 than 50 + age group (34.7 vs. 22.6 per 1000, p-value < 0.0001). Conclusions The mean rate of reported deaths was higher among men in most models despite adjusting for VLS. Further exploration into differences in care-seeking behaviors; coverage of screening, prophylaxis, and/or treatment of opportunistic infections; and more extensive testing options for men to include CD4 is recommended.